Freedom of the Markets versus Good Governance: Experiences in Central Europe - Muraközy, Laszlo (Competitio, 2010)
The market and the state, operation and characteristics of two institutions of key importance in the modern mixed economies, are investigated for the former socialist countries in this study. After two decades it can be seen more clearly what system has been established in the region, how it operates, and what its characteristics are. In the first part of the with the help of international comparisons we examine how free the market is, how good the rules are, and how much they help, or hinder, the fulfilment of its function. From an other aspect we compare the scope of the good governance and the size, the freedom and efficiency of the state. According to the evidence of the international studies examined, the former socialist countries established the forms of the market institutional system relatively quickly, but the operation and quality of these lagged significantly behind those of the developed countries. Also important conclusion of the study is that by the first decade of the millennium the characteristics of the former socialist countries are increasingly diverging from one another. Both the characteristics of the earlier socialism, and the more distant historical past which can be caught in the act within it, had and have an effect on the economic and social systems now established in Eastern and Central Europe. Journal of Economic Literature (JEL) codes: H1, P17, P27, P35